2011
DOI: 10.1002/smll.201100448
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Aligned Sub‐10‐nm Nanogap Electrode Array for Large‐Scale Integration

Abstract: A novel approach to creating a gap on the nanometer scale between two adjacent electrodes of the same or different metals is described. The gap size can be well controlled through sidewall coverage in a self-aligned manner and it can be tuned from 60 nm down to 5 nm with high reproducibility. This technique is fully compatible with traditional microfabrication technology and it is easily implemented to fabricate a nanogap electrode array for integration purposes. An array of short-channel single-walled carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The patterning resolution that can be achieved using a-lith compares favourably with the very few reports of aligned asymmetric nanogaps in the literature45, which have utilized e-beam lithography to achieve the requisite registration of the two metals. Using a combination of optical lift-off lithography, e-beam lithography, plasma-enhanced vapour deposition and chemical etching, Gao et al 4 reported an 11-step route to asymmetric electrodes capable of yielding well aligned nanogaps of Ti and Au down to 5 nm.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The patterning resolution that can be achieved using a-lith compares favourably with the very few reports of aligned asymmetric nanogaps in the literature45, which have utilized e-beam lithography to achieve the requisite registration of the two metals. Using a combination of optical lift-off lithography, e-beam lithography, plasma-enhanced vapour deposition and chemical etching, Gao et al 4 reported an 11-step route to asymmetric electrodes capable of yielding well aligned nanogaps of Ti and Au down to 5 nm.…”
Section: Discussionmentioning
confidence: 70%
“…Using a combination of optical lift-off lithography, e-beam lithography, plasma-enhanced vapour deposition and chemical etching, Gao et al 4 reported an 11-step route to asymmetric electrodes capable of yielding well aligned nanogaps of Ti and Au down to 5 nm. Guillorn et al 5 meanwhile reported a sophisticated procedure, utilizing high-resolution e-beam lithography, two stages of reactive ion etching, thermal and electron gun physical vapour deposition of the metals and lift-off pattern transfer to achieve asymmetric electrode pairs of Au and Pt, Ti, Pd or Al with interelectrode spacings of 6 nm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods have been applied to form nanogaps with specic widths, like electron-beam lithography, 7,8 electroplating, 9 molecular lithography, [9][10][11][12] shadow evaporation, 13 and electromigration, 14 among others. [15][16][17][18][19][20] In a previous study, 21 we successfully developed a method for nanogap fabrication in which a voltage is applied during metal deposition, inducing the electromigration of the metals. We applied this method to form self-aligned nanogaps as small as 1 nm in width and found that the gap width could be controlled by changing the magnitude of the applied voltage.…”
Section: Introductionmentioning
confidence: 99%
“…The patterning of CNTs is particularly relevant for the preparation of nanoscale devices and sensors based on the outstanding electronic properties of CNTs 2. Patterned arrays of CNTs are usually obtained by first patterning a catalyst onto a suitable substrate, for example by evaporation through a mask or alternatively by soft lithographic methods such as μCP.…”
Section: Introductionmentioning
confidence: 99%